Rabies virus glycoprotein variants display different patterns in rabies monosynaptic tracing - Mori, Takuma; Morimoto, Kinjiro (Frontiers in Neuroanatomy, 2014)
Rabies virus (RV) has been widely used to trace multi-synaptic neuronal circuits. The recent development of glycoprotein-deficient rabies virus (RV-ΔG) expressing various proteins has enabled analyses of both the structure and function of neuronal circuits. The main advantage of RV-ΔG is its ability to trace monosynaptic circuits by the complementation of rabies virus glycoprotein (RVG), but it has the disadvantage of cytotoxicity. Several strain variants of rabies virus have different biological characteristics, such as synaptic spreading and cytotoxicity, mainly due to amino acid mutations in RVG. We developed an improved protocol for the production of a highly attenuated strain of RV-ΔG and assessed whether RVG variants affect rabies monosynaptic tracing and the health of infected neurons. We demonstrated that 1) rabies monosynaptic tracing with RVG variants traced different subsets of presynaptic partners, 2) RVG of the attenuated strain also labeled astrocytes, and 3) the cytotoxicity of RV-ΔG did not depend on RVG but on RV-ΔG. These findings indicate that RVG variants are an important determinant of rabies monosynaptic tracing.